2018
DOI: 10.1080/03003930.2017.1411811
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan challenges and reform pressures across Europe – the perspectives of city mayors

Abstract: Oliver Dlabac leads the research group on Local Democracy at the Centre for Democracy Studies Aarau and teaches on decentralisation at the University of Zurich. He has published on local and regional democracy in Switzerland and is currently leading a research project on the democratic foundations of urban planning in the city regions of Birmingham, Lyon and Zurich. Lluís Medir lectures in the Department of Political Science at the University of Barcelona, Spain. His research interests include local government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Longer tenure reduces uncertainty and promotes decision-making based on long-term considerations of the collective benefits of collaboration (Brown and Potoski 2003;Clingermayer and Feiock 2014;Feiock 2007, p. 55;Hawkins 2017;Hefetz, Warner, and Vigoda-Gadot 2012, p. 756). Also ideological changes affect IMC; evidence suggests that right-wing mayors tend to cooperate less (Bel, Fageda, and Mur 2014;Dlabac et al 2018), but this finding still remains to be confirmed in other parts of the world.…”
Section: Political Institutions In Metropolitan Local Governmentsmentioning
confidence: 99%
“…Longer tenure reduces uncertainty and promotes decision-making based on long-term considerations of the collective benefits of collaboration (Brown and Potoski 2003;Clingermayer and Feiock 2014;Feiock 2007, p. 55;Hawkins 2017;Hefetz, Warner, and Vigoda-Gadot 2012, p. 756). Also ideological changes affect IMC; evidence suggests that right-wing mayors tend to cooperate less (Bel, Fageda, and Mur 2014;Dlabac et al 2018), but this finding still remains to be confirmed in other parts of the world.…”
Section: Political Institutions In Metropolitan Local Governmentsmentioning
confidence: 99%
“…Three broad schools of metropolitan governance have been identifiedreform school, public choice theory and new regionalismbut the assumptions of each partly influence the approaches of policy makers (Dlabac et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For all this, the relentless pace of global urban change poses fundamental questions about how best to plan and govern metropolitan regions. The problem facing metropolitan regions-especially for those with policy and decision-making responsibilities-is that these spaces are typically reliant on inadequate urban economic infrastructure and fragmented planning and governance arrangements (Dlabac et al 2018;Fedeli 2017;Harrison and Hoyler 2014;Kantor et al 2012). As the demand for more appropriate, widely understood to mean more flexible, networked and smart, forms of planning and governance has increased, new expressions of territorial cooperation and conflict continue to emerge around issues and agendas of infrastructure investment, housing, land-use planning, environmental management and other social forms of collective provision.…”
mentioning
confidence: 99%